2013
DOI: 10.2174/1573406411309050006
|View full text |Cite
|
Sign up to set email alerts
|

Modified Silica Matrices for Controlled Release of Cephalexin

Abstract: SBA-15 type ordered silicas possessing amino groups attached onto their surfaces were prepared by using two different functionalization methodologies. These matrices were used for the cephalexin adsorption from aqueous solution and further kinetic study of its release into physiological solution. The materials were characterized by nitrogen adsorption/ desorption, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), X-Ray photoelectron spectrometry (XPS) and thermo analytical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Loading assays were carried out by soaking powdered samples in water (pH $ 6). 52 Elemental chemical analyses were used to quantify the amount of CPX loaded into the different mesoporous samples. The results are shown in Table 4, 11.2 and 12.7 mg g À1 being the amounts of CPX loaded for SBA-15 and SBA-Zwitter, respectively.…”
Section: In Vitro Antibiotic Adsorption and Releasementioning
confidence: 99%
“…Loading assays were carried out by soaking powdered samples in water (pH $ 6). 52 Elemental chemical analyses were used to quantify the amount of CPX loaded into the different mesoporous samples. The results are shown in Table 4, 11.2 and 12.7 mg g À1 being the amounts of CPX loaded for SBA-15 and SBA-Zwitter, respectively.…”
Section: In Vitro Antibiotic Adsorption and Releasementioning
confidence: 99%
“…In previous work we demonstrated that cephalexin could successfully be loaded on SBA-15 mesoporous silica [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the fastest release was observed for CPX/SBA-15-Pr-SO 3 H since there are not interactions occurred between the CPX molecules and the sulfonic acids on the surface, despite the presence of an amino group in the CPX molecule 78. In another publication, it was demonstrated that, post-functionalization SBA-15-Pr-NH 2 could enhance the long-term CPX delivery in comparison with the co-condensation procedure 79. …”
mentioning
confidence: 96%